Penguatan Pembelajaran Mata Matematika tentang Bilangan dan Persamaan Kuadrat Siswa SMAN 1 Gowa melalui Mata Garuda LPDP Sulawesi Selatan - Syamsuddin Mas'ud (Jurnal Abdi Bangsa, 2025)
This community service program aims to strengthen the fundamental mathematical understanding of students at SMAN 1 Gowa, particularly on the topics of number systems and quadratic equations. The program was conducted over five in-person sessions during November, using lecture and question-and-answer methods supported by classroom facilities, a laptop, and a smart TV. Each meeting was followed by a formative test to monitor students’ progress. The results indicate improvements in students’ abilities to operate with numbers, understand algebraic expressions, and solve quadratic equations systematically. The school’s role in providing facilities and coordinating student participation contributed significantly to the smooth implementation of the program. This activity is expected to serve as a simple yet effective intervention model for strengthening students’ basic mathematical concepts. Moving forward, improving students’ discipline,particularly in attendance and preparedness, will be crucial for achieving more optimal outcomes.